2011
DOI: 10.1264/jsme2.me10198
|View full text |Cite
|
Sign up to set email alerts
|

Roles of Pseudomonas aeruginosa Autoinducers and their Degradation Products, Tetramic acids, in Bacterial Survival and Behavior in Ecological Niches

Abstract: Pseudomonas aeruginosa, an opportunistic pathogen, is known to mainly use N-acylhomoserine lactones (AHLs) as autoinducers. Recent progress in this field demonstrated that not only AHLs, but also their degradation products, tetramic acids, may have some biological activities. The present study examined the roles of Pseudomonas autoinducers and tetramic acids in bacterial survival and behavior in ecological niches. P. aeruginosa autoinducers and the tetramic acid derivatives were chemically synthesized, and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 41 publications
1
7
0
Order By: Relevance
“…These data are broadly in agreement with the staphylococcal MICs for 5 and 7 reported by Lowery et al 14 Interestingly, the shorter chain compound 5-HE-C4-TMA 3 , which we found was not active against S. aureus , has been reported to kill P. aeruginosa (15) but not C. difficile . 13 TMAs with 3-acyl chains of 10–14 carbons inhibited growth and agr with differences between the MIC and IC 50 values ranging from little different (e.g., 5-HE-C14-TMA 8 ) to 5-fold (e.g., 5-HE-C11-TMA 6 ).…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…These data are broadly in agreement with the staphylococcal MICs for 5 and 7 reported by Lowery et al 14 Interestingly, the shorter chain compound 5-HE-C4-TMA 3 , which we found was not active against S. aureus , has been reported to kill P. aeruginosa (15) but not C. difficile . 13 TMAs with 3-acyl chains of 10–14 carbons inhibited growth and agr with differences between the MIC and IC 50 values ranging from little different (e.g., 5-HE-C14-TMA 8 ) to 5-fold (e.g., 5-HE-C11-TMA 6 ).…”
Section: Resultssupporting
confidence: 93%
“…23 Since iron has been reported to abolish the antibacterial activity of 5 toward C. difficile and P. aeruginosa , 13,15 we synthesized TOA (Table 3, 14 – 18 ; Table S2, S17 – S24 ) variants of the TMAs in which the ring nitrogen is replaced with oxygen. We predicted that the tetronic acid structure would not chelate iron, as it largely exists as a 4-enolic tautomer 24 as opposed to the TMA structure where the 3-exoenolic tautomer in ( Z )-configuration predominates.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Examination of dormant microbes is required for comprehensive understanding of microbial communities, because dormant microbes provide clues to the hidden function of microbial community and they may contribute to stability of microbial ecosystems. Recently, physiological states in response to environmental stress have been well-studied in microbial ecology (16, 22, 67, 69). …”
Section: Unexpected Microbial Diversity/functionmentioning
confidence: 99%